DINAMIKA JABATAN 20 TAHUN KEPALA DESA - Febri Anggita Ruiyati; Yusuf Adam Hilman (Jurnal Partisipatoris, 2023)
The village head asked for an extension of office for 9 years with 3 terms equal to a term of office of 27 years because for them a term of office of six years actually sharpened the competition between village head candidates. According to him, a nine-year term of office for village heads can reduce conflict in political competition in village head elections. Apart from the question of extending the term of office, village heads spoke out regarding village sovereignty. There are reasons for extending the term of office of the village head, one of which is to maximize village development. The reason is, the election of the village head causes polarization in the village to be quite prolonged. Therefore, it is better if the village head's term of office is extended to nine years. This research aims to analyze the dynamics of village heads' requests to extend their terms of office to 20 years or 3 terms. Discusses the background to the request to extend the position of village head, related laws, and suggestions for the government. This research uses qualitative methods, namely descriptive research and uses concrete data analysis. The position of village head has lasted more than 20 years, this is a deviation from the 1945 Constitution because it narrows democracy in the village. This also causes injustice in occupying leadership positions in village government and gives rise to exploitation of positions by certain people. The researcher advised the government to reject the proposal to extend the Village Head's term of office to 9 (nine) years and can be served for 3 (periods). The government should focus more on structuring village government in order to realize village development in order to improve the quality of life and welfare of village communities.